External lesions and their relationship with alcohol consumption in patients attending in an emergency hospital in Lima, Peru - Villar, Emily (2022)
Objective: To describe demographic, temporal and spatial relationships of external lesions (EL) with alcohol consumption in patients attending an emergency hospital in Lima. Methods: Retrospective study of patients with EL attended at Hospital de Emergencias Casimiro Ulloa from 2014-2016 including information on police investigation. Logistic regression analysis was carried-out to evaluate association between type of EL and alcohol consumption. Results: The relationship of alcohol consumption and EL was stronger in males and from Thursday to Sunday. Contusions instead of stab wounds were more likely when the victim was male from 15-38 years of age and when had occurred from 00:00 to 18:00 from Thursdays to Sundays. EL occurred more frequently near main avenues at no more than 500 meters from alcoholic beverages were sold. Conclusions: Victims of EL are more likely to be males not necessarily living in the district where the aggression occurred, which tended to happen near main avenues close to where alcoholic beverages are offered. Alcohol consumption could not be ruled-out as a risk factors for EL.